2010
DOI: 10.1590/s0100-69162010000600020
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento das águas do processamento dos frutos do cafeeiro em filtro anaeróbio seguido por sistema alagado construído: II - remoção de nutrientes e compostos fenólicos

Abstract: RESUMO: Seis sistemas de tratamento foram compostos por três filtros anaeróbios com escoamento descendente, seguidos por seis sistemas alagados construídos (SACs), sendo avaliados, sob o ponto de vista operacional, no tratamento da água residuária do processamento dos frutos do cafeeiro (ARC). Os filtros foram confeccionados em PVC (1,5 m de altura e 0,35 m de diâmetro) e preenchidos com brita n o 2 e os SACs foram constituídos por caixas de madeira (1,5 m de comprimento, 0,4 m de altura e 0,5 m de largura), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
0
2
4
Order By: Relevance
“…The levels of removal of TS and TSS obtained in this research were higher than those observed by Reinaldo et al [30] consisting of a decant digester with a biological filter followed by constructed wetland and solar reactor, which obtained average efficiencies of removal of TS and TSS of 61 and 99% respectively; and [31] studying treatment system in ANF followed by two constructed wetlands, observed average efficiencies of removal of TS and TSS of 29 and 74% respectively. Fia et al [31] associated the low efficiency of TS and TSS removal to low temperatures (average of 17.4 ± 2.2°C) recorded during the experimental period, which according to them, kept the fluid viscosity high, which resulted in lower sedimentation velocity of the biomass produced. Low concentration of TSS observed in this research can be beneficial in rural areas for reuse in agriculture, since the chances of clogging irrigation equipment, such as emitter, would be lower.…”
Section: Resultscontrasting
confidence: 72%
“…The levels of removal of TS and TSS obtained in this research were higher than those observed by Reinaldo et al [30] consisting of a decant digester with a biological filter followed by constructed wetland and solar reactor, which obtained average efficiencies of removal of TS and TSS of 61 and 99% respectively; and [31] studying treatment system in ANF followed by two constructed wetlands, observed average efficiencies of removal of TS and TSS of 29 and 74% respectively. Fia et al [31] associated the low efficiency of TS and TSS removal to low temperatures (average of 17.4 ± 2.2°C) recorded during the experimental period, which according to them, kept the fluid viscosity high, which resulted in lower sedimentation velocity of the biomass produced. Low concentration of TSS observed in this research can be beneficial in rural areas for reuse in agriculture, since the chances of clogging irrigation equipment, such as emitter, would be lower.…”
Section: Resultscontrasting
confidence: 72%
“…As conchas podem ser utilizadas, por exemplo, para constituir meio poroso e de suporte em sistemas alagados construídos (FIA et al, 2010a;FIA et al, 2010b;MATOS et al, 2010b) podendo aumentar a eficiência do sistema no que se refere à remoção de P. A necessidade de remoção de P de águas residuárias decorre do fato de que, se esse elemento químico não for removido eficientemente, poderá proporcionar aumento em suas concentrações em corpos hídricos onde forem lançadas. O aumento na concentração de P solúvel nas águas, proporcionando a eutrofização do meio aquático e, como consequência, o desenvolvimento excessivo de algas e macrófitas, o que pode prejudicar os diversos usos benéficos da água, inclusive o potável, além de causar mortandade dos peixes e outros organismos aquáticos.…”
Section: Adsorção De Fósforo Em Farelo De Vôngoleunclassified
“…Los valores de pH obtenidos en M1 y M2 están por debajo a los de la normatividad, esto se puede deber a la presencia de ácidos orgánicos en el café, así como procesos de fermentación que pueden generar la producción de ácidos y ocasionar la disminución del pH [22]. Autores como Fia et al [23] encuentran un pH de 3,44 (± 0,16), Alvarez et al [24] registran un pH de 3,8 y Rodríguez et al [25] y Olvera y Gutiérrez [26] encontraron valores de 4,6, teniendo una característica ácida en todos los casos, incluyendo el de la presente investigación. En cuanto a aguas residuales domésticas, Vásquez Sarria et al [27] encontraron que oscila entre 6,1 y 7,7 siendo mayor (3,98-4,05) al obtenido en esta investigación.…”
Section: Resultados Y Discusiónunclassified